(untitled) (Global Journal of Science Frontier Research, 2012)
Breadfruit is a valuable food resource, but its usage is limited by poor storage properties of the fresh fruit. Therefore , there is need for conversion into flour to provide a more stable storage form as well as increasing its versatility. Breadfruit flour was processed into two conventional food forms ; namely cake and chin-chin. The cake and chin-chin samples were made from blends of 10% , 20%, 30%, 40% and 100% breadfruit flour. The proximate composition and sensory evaluation were determined. The proximate composition showed that 40% breadfruit flour blend had highest protein content (1.39%). The value for 100% wheat flour was 1.05%, while that of breadfruit flour only was 1.31%; this showed that supplementation of breadfruit flour would improve the protein nutritional quality of the products. The moisture content of the samples varied between 12.77% and 9.57%, decreasing with increasing substitution of breadfruit flour , hence prolonging the shelf-life. Protein content had range of (1.05-1.39%) and ash content (0.94-1.12%).